Layanan Bimbingan Kelompok Menggunakan Media Pembelajaran Tebak Kata Untuk Meningkatkan Kontrol Diri Penggunaan Gadget Siswa - Ifna, Tria (Program Studi Bimbingan dan Konseling FKIP UMSU, 2024)
This research was conducted to describe the difference in scores in increasing self-control in using gadgets in experimental group students before and after being treated with group guidance services using word guessing learning media. Meanwhile, the control group was given treatment before and after with group guidance services. This research is quantitative research with the type of experimental research. The object of this research was class X TKJ 1 SMK YPK Medan. The data collection technique in this research used a questionnaire for students to determine self-control in using gadgets. The results of this research show that students have low self-control in using gadgets, resulting in students' ability to control themselves in using gadgets, especially in the school environment and while studying. The analysis test results used the Wilcoxon Signed Ranks Test and the Kolmogorov Smirnov Two Independent Samples analysis test. Thus, based on the results of the research conducted, among others: (1) there is a significant difference in self-control of student gadget use in the experimental group before (pretest) and after (posttest) with group services using word guessing learning media. (2) there is a significant difference in students' self-control of gadget use in the control group before (pretest) and after (posttest) with group guidance services. (3) there is a significant difference in students' self-control of gadget use in the experimental group and the control group who were given treatment.